KAJIAN PEMBENTUK KARAKTERISTIK LANSKAP MELAYU PADA LANSKAP KOTA PEKANBARU, RIAU - M. Arthum Artha; . Nurhayati; Aris Munandar (Jurnal Lanskap Indonesia, 2013)
ABSTRACTThe identity of a city demonstrates interaction between human and landscape that dominated by manmade environment with high density of population and particular background of social and culture as well as the activity and production process not rely on nature. This identity can increase and corroborate the value of city. Pekanbaru is the capital city of Riau Province that located in Sumatera Island with Malay character. One of the Riau Province and Pekanbaru government visions is to be the central of Malay culture in South East Asia in 2020. The aims of this research were to examine trend of the character of Malay landscape, to identify the existing of landscape elements which belong to Malay character, to analyze the main elements of Malay landscape character and to propose protection of the Malay characteristics and application of each element for development of Pekanbaru City. Methods of this research were collecting information and data of the history of Malay in Pekanbaru through indeep interview, field observation, literature study and Analytical Hierarchy Process (AHP). The results of this study were identification of Malay landscape characteristics in Pekanbaru City mainly based on period of Siak Kingdom at Senapelan (1762-1783) and Province at Negeri Pekanbaru (1891-1916) the existence of main elements that shaping Malay landscape character, AHP decision result as well as application and for guidance in developing urban landscape through determination, protection and development.Keywords: Malay landscape, landscape characteristic , historical urban landscape, Pekanbaru city